Krisis Kepemimpinan dan Tanggung Jawab Etis-Teologis dalam Bencana Ekologis Sumatera - Harlinton Simanjuntak (Sekolah Tinggi Teologi Parakletos Tomohon, 2026)
Abstract: The ecological disaster that occurred in Aceh, North Sumatra, and West Sumatra in November 2025 revealed an ethical-theological crisis in political leadership practices in Indonesia. The narrative friction between the government and the community, as well as various controversial legal and political policies, form the background of this study. Using a literature-based research method grounded in Colossians 3:17 and a social hermeneutic approach, this study analyses the socio-legal-political dynamics behind these disasters in relation to moral responsibility in governance. The results of the study reveal five main issues: deforestation and environmental destruction, weak disaster risk mitigation, problems with environmental law enforcement, unpreparedness and lack of responsiveness in disaster management, and ineffective and irrelevant public communication. These findings confirm that the ecological crisis in Sumatra is not merely a natural phenomenon, but a manifestation of leadership failure. A comprehensive evaluation of natural resource management is needed to realise environmental policies that are fair, sustainable, and in line with the principles of ethical-theological responsibility. Abstrak: Bencana ekologis yang terjadi di Aceh, Sumatera Utara, dan Sumatera Barat pada November 2025 memperlihatkan adanya krisis etis-teologis dalam praktik kepemimpinan politik di Indonesia. Friksi narasi antara pemerintah dan masyarakat serta berbagai kebijakan hukum dan politik yang kontroversial menjadi latar belakang penelitian ini. Melalui metodo riset literatur berbasis prinsip Kolose 3:17 dan pendekatan hermeneutika sosial, penelitian ini menganalisis dinamika sosial-hukum-politik di balik bencana tersebut dalam kaitannya dengan tanggung jawab moral dalam tata kelola pemerintahan. Hasil penelitian menunjukkan lima persoalan utama: deforestasi dan perusakan lingkungan hidup, lemahnya mitigasi risiko bencana, masalah penegakan hukuk lingkungan, ketidaksiapan dan ketidaksigapan penanggulangan bencana, serta komunikasi publik yang tidak efektif dan relevan. Temuan ini menegaskan bahwa krisis ekologis di Sumatera bukan sekadar fenomena alam, melainkan manifestasi dari kegagalan dalam kepemimpinan. Diperlukan evaluasi yang menyeluruh terhadap pengelolaan sumber daya alam untuk mewujudkan kebijakan lingkungan yang adil, lestari, dan sesuai dengan prinsip tanggung jawab etis-teologis